« On ne peut pas empêcher les concepts de voyager » : un entretien avec Christine Delphy - Marc Calvini-Lefebvre (Revue Française de Civilisation Britannique)
The concept of patriarchy which is at the heart of this special issue, owes a great deal to the work of French sociologist Christine Delphy. In 1970, she published a pioneering analysis of the free labour that women did in the home, arguing that it was the economic foundation of their subordination to men, whatever their social class. In the face of this “sex-specific oppression”, women must prioritise, she argued, the “total destruction of the system of patriarchal production and reproduction, a system which she famously called the “principal enemy” of the women’s liberation movement. We wished to meet her to ask her about the genesis of this concept, its articulation with other notions and concepts that have been put forward to make sense of inequalities between women and men, and the recent proliferation of its usage in pop culture and the mainstream media.